2017
DOI: 10.5194/bg-2017-185
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of ocean acidification and elevated temperature on growth of calcifying tubeworm shells (<i>Spirorbis spirorbis</i>): An <i>in-situ</i> benthocosm approach

Abstract: <p><strong>Abstract.</strong> The calcareous tubeworm <i>Spirorbis spirorbis</i> is a wide-spread serpulid species in the Baltic Sea, where it commonly grows as an epibiont on brown macroalgae (genus <i>Fucus</i>). It lives within a Mg-calcite shell and could be affected by ocean acidification and temperature rise induced by the predicted future atmospheric CO<sub>2</sub> increase. Howe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…However, to be buffered, the benefits during the day need to be great enough to offset the negative effects of respiration at night. In addition, the tube worm response can be driven by temperature (Campbell and Fourqurean, 2014;Ni et al, 2017). For example, S. spirorbis, in the laboratory, had reduced recruitment on a fucoid alga at extreme P CO2 (3150 µatm) but not at moderate levels (1200 µatm; Saderne and Wahl, 2013).…”
Section: Ecological Relevancementioning
confidence: 99%
See 1 more Smart Citation
“…However, to be buffered, the benefits during the day need to be great enough to offset the negative effects of respiration at night. In addition, the tube worm response can be driven by temperature (Campbell and Fourqurean, 2014;Ni et al, 2017). For example, S. spirorbis, in the laboratory, had reduced recruitment on a fucoid alga at extreme P CO2 (3150 µatm) but not at moderate levels (1200 µatm; Saderne and Wahl, 2013).…”
Section: Ecological Relevancementioning
confidence: 99%
“…An in situ benthocosm study, using the same species, concluded that early life stages are promoted by moderately warm temperatures. However, high temperatures exacerbate tube dissolution and do not alter growth when water is undersaturated with respect to CaCO 3 (Ni et al, 2017) Table 3 for statistical results).…”
Section: Ecological Relevancementioning
confidence: 99%